Letter from R. F. Stockton to James Curtis Booth, July 20, 1857 - Stockton, Robert Field (1857)
A request for a report from James Curtis Booth (1810-1888).
Keywords: Booth, James Curtis, 1810-1888; United States Mint; Mint of the United States